Nghiên cứu ảnh hưởng của rủi ro cảm nhận đến thái độ và ý định sử dụng dịch vụ tour bốn đảo của du khách quốc tế tại Nha Trang - Lê Chí, Công (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This study examines the role of perceived risk in explaining attitude and intention to use the tour-four-islands service of international tourists to Nha Trang. By collecting a sample of 450 international tourists and using the extended theory of planned behavior (TPB), the confirmation factor analysis (CFA), and structural equation modeling (SEM) for testing the relationships between the constructs and evaluate their reliability as well as convergent and discriminant validity, the research findings show that the two constructs, subjective norm and perceived behavior control, are found to exert positive effects on tourists’ intention to use the tour-four-islands service. Specifically, such a novel construct as perceived risk introduced to the TPB literature has a direct and negative impact on both their attitude and intention. The results provide useful information to tour agencies, so sound policies can be formulated to reduce risk and enhance the positive attitude as well as intention to use the tour-four-islands service.
Keywords: Perceived risk; Attitude; Intention; TPB; Tour service